An Online College Near Me: Exploring the Institutional Factors of E-Learners’ Local Orientation - Yoon, Hyungjoo (International Review of Research in Open and Distributed Learning, 2019)
One advantage of online learning settings relative to conventional classrooms is their anytime, anywhere accessibility. While online education programs provide students with flexible learning opportunities free from the restrictions of geographic location, a consistently growing number of students who prefer to learn exclusively online still choose nearby colleges. The choice to attend a local college by exclusively online learners is an interesting phenomenon, because most of these students rarely visit campus at any point in the process of obtaining their degrees. This study aims to explain this localized distance student enrollment pattern using Integrated Postsecondary Education Data System data and Homeland Infrastructure Foundation-Level Data from the fall of 2016. This research uses a multiple regression technique to explain the relationship between institutional factors and localized distance student enrollment patterns in the US. This study utilizes the C2Q (cost, convenience, and quality) model to explain the local orientation of e-learners. The findings show that convenience and quality of education are significantly associated with each local institution’s share of exclusively online learners in the same state.